Hierarchical Control Planning Based on the Film 'Avatar: The Way of Water' to Minimize Work Accidents Among Fishermen - Ridwan Gucci, Dinda Okta Dwiyanti; Nalendra, Muhammad Adi Sukma; Sarena, Prisilia Cahaya Putri; Saleh, Yohaneis (TALENTA Publisher, 2024)
Cultivating health and occupational safety among fishermen can involve various strategies, such as reviewing movies for insights. These films serve as reflections of the relevance to the cultural aspects of fishermen's health and safety, contributing to the Health and Occupational Safety Triangle or Hierarchy Control. Hierarchy Control, a sequential risk reduction process, encompasses elimination, substitution, design, administration, and personal protective equipment (PPE). The study aims to reduce or eliminate work accidents for fishermen, utilizing planning hierarchy control with an approach involving Macro Ergonomics, Semiotics, and the Fogg Behavior Model. Findings identify a minimal health and safety culture during service, leading to the design of three hierarchy controls: Standard Operating Procedures (SOPs) for machines and equipment (administrative control), ship closures for noise reduction (engineering controls), and the implementation of Personal Protective Equipment. However, elimination and substitution remain challenging to implement in daily service activities.